A new Score for Predicting Immune Checkpoint Inhibitor-Associated Thrombosis in Cancer Patients - Xiaotong Xia MS; Shu Chen MS; Chengwei Huang BS; YanRong Ye BS; Yun Shen BS; Lumin Wang MS (Clinical and Applied Thrombosis/Hemostasis)
Purpose This study aims to develop a scoring system tailored for Asian populations through quantifying VTE risk in a cohort of hospitalized cancer patients receiving immune checkpoint inhibitors. Methods We retrospectively analyzed 1171 patients treated with PD-1/PD-L1 inhibitors at Zhongshan Hospital (Xiamen), Fudan University between January 2021 and December 2023. We gathered information on every patient from the electronic database of the hospital and follow-up.The collected data were statistically analyzed to obtain risk factors for for VTE and validation of the score. Finally, we validated the precision of the model in prediction. Results Based on these findings, we developed the L2HSDK score,that identified seven independent risk factors for VTE:liver cancer, smoking, diabetes mellitus, liver dysfunction, cardiovascular history, and a Khorana Risk Score ≥ 3. The patients were divided into low, moderate, and high VTE risk groups. Significant differences in VTE incidence were observed across these groups, with the high-risk group showing a markedly higher risk. The validation of the model demonstrates the precision of the L2HSDK score in prediction. Conclusion The L2HSDK score offers a more precise and tailored method for assessing VTE risk in cancer patients receiving PD-1/PD-L1 inhibitors therapy in mainland China, surpassing the widely used Khorana Risk Score by accounting for regional and treatment-specific factors.